Costs of ambulatory care related to female pelvic floor disorders in the United States - Sung, Vivian W. (2010)
OBJECTIVE: To evaluate trends in costs of ambulatory care related to female pelvic floor disorders (PFD) in the United States. STUDY DESIGN: We used the National Ambulatory Medical Care Survey for national estimates of ambulatory visits in the United States. PFD-related visits were based on ICD-9 codes. Visits were assigned an Evaluation and Management (E/M) code and costs were estimated using national average Medicare allowances for physician services. We converted costs to 2006 dollars using the physicians’ services component of the Consumer Price Index and compared the average annual costs between 1996–1997 and 2005–2006. RESULTS: The average annual cost of ambulatory physician services related to PFDs was $190 million in 1996–1997 and $298 million in 2005–2006 (P=.05). Adjusting for deductibles and co-payments, these estimates increase to $262 million in 1996–1997 and $412 million in 2005–2006. CONCLUSIONS: The cost of ambulatory care related to female PFDs is significant and is increasing.